Arete in Plato and Aristotle Selected Essays from the 6th Interdisciplinary Symposium on the Hellenic Heritage of Sicily and Southern Italy - Brown, Ryan M. (Parnassos Press - Fonte Aretusa, 2022)
Arete is a central yet elusive concept in ancient Greek culture. Traditionally associated with the strength and skill of heroes, warriors and athletes, arete evolved over the course of ancient Greek history to become a primary focus of ethical and political reflection and debate. For ancient Greek philosophy, arete (traditionally translated as "virtue") was the essential object of human admiration and striving, and even the key to happiness. Despite this shared conception, deep disagreements persisted among ancient thinkers about what exactly arete is, who has it, and why it is so valuable. A companion volume, Ageless Arete, provides a broad overview of the diverse roles played by arete in ancient Greece and Rome. The present volume, Arete in Plato and Aristotle, offers a focused exploration of perhaps the two most innovative and influential contributors to ancient philosophical debates about arete. Plato and Aristotle took the concept of arete as the starting point for investigations of the human soul, the good life, the nature of knowledge, the goals of education, and the role of politics and culture in nurturing human excellence. Their work continues to inspire reflection on these fundamental questions today, as the fourteen new essays collected here demonstrate.